1H MRS characterization of neurochemical profiles in orthotopic mouse models of human brain tumors. (13th November 2014) - Hulsey, Keith M.; Mashimo, Tomoyuki; Banerjee, Abhishek; Soesbe, Todd C.; Spence, Jeffrey S.; Vemireddy, Vamsidhara; Maher, Elizabeth A.; Bachoo, Robert M.; Choi, Changho
<x xml:space="preserve">Abstract</x> Glioblastoma (GBM), the most common primary brain tumor, is resistant to currently available treatments. The development of mouse models of human GBM has provided a tool for studying mechanisms involved in tumor initiation and growth as well as a platform for preclinical investigation of new drugs. In this study we used 1H MR spectroscopy to study the neurochemical profile of a human orthotopic tumor (HOT) mouse model of human GBM. The goal of this study was to evaluate differences in metabolite concentrations in the GBM HOT mice when compared with normal mouse brain in order to determine if MRS could reliably differentiate tumor from normal brain. A TE =19 ms PRESS sequence at 9.4 T was used for measuring metabolite levels in 12 GBM mice and 8 healthy mice. Levels for 12 metabolites and for lipids/macromolecules at 0.9 ppm and at 1.3 ppm were reliably detected in all mouse spectra. The tumors had significantly lower concentrations of total creatine, GABA, glutamate, total N‐acetylaspartate, aspartate, lipids/macromolecules at 0.9 ppm, and lipids/macromolecules at 1.3 ppm than did the brains of normal mice. The concentrations of glycine and lactate, however, were significantly higher in tumors than in normal brain. Copyright © 2014 John Wiley & Sons, Ltd.